Handbook of sexuality-related measures - Milhausen, Robin R.; Davis, Clive M.; Yarber, William L. (Routledge hadbooks, 2020)
Abuse and pedophilia -- Adolescents -- Affect and emotions -- Arousal and arousability -- Attitudes, beliefs, and cognitions -- Body image and sexualization -- Clinical self-efficacy -- Coercion and consent -- Communication -- Compulsivity, hypersexuality, and addiction -- Condoms -- Desire and interest -- Families and sexuality -- Gender (clinical) -- Gender identity -- Gender roles, norms, and expressions -- HIV/STI attitudes and behaviors -- Identity and orientation -- Love and relationships -- Motivations -- Pleasure, satisfaction, and orgasm -- Sadism and masochism -- Self-concept and self-esteem -- Sexual comfort and erotophobia/erotophilia -- Sexual function, dysfunction, and difficulties -- Sexual prejudice -- Sexual scripts and sexual double standard -- Sexually explicit material and online sexual activity -- Sociosexuality and sexual sensation seeking.